A cryopreservation method for bioengineered 3D cell culture models. (1st July 2022) - Herrero-Gómez, Alba; Azagra, Marc; Marco-Rius, Irene
Abstract: Technologies to cryogenically preserve (a.k.a. cryopreserve) living tissue, cell lines and primary cells have matured greatly for both clinicians and researchers since their first demonstration in the 1950s and are widely used in storage and transport applications. Currently, however, there remains an absence of viable cryopreservation and thawing methods for bioengineered, three-dimensional (3D) cell models, including patients' samples. As a first step towards addressing this gap, we demonstrate a viable protocol for spheroid cryopreservation and survival based on a 3D carboxymethyl cellulose scaffold and precise conditions for freezing and thawing. The protocol is tested using hepatocytes, for which the scaffold provides both the 3D structure for cells to self-arrange into spheroids and to support cells during freezing for optimal post-thaw viability. Cell viability after thawing is improved compared to conventional pellet models where cells settle under gravity to form a pseudo-tissue before freezing. The technique may advance cryobiology and other applications that demand high-integrity transport of pre-assembled 3D models (from cell lines and in future cells from patients) between facilities, for example between medical practice, research and testing facilities.